Monopoly Game Of Aksara Jawa As Teaching Tool In Javanese Language Learning - Pratiwi, Amalia Dyah; Sumilah, Sumilah (Elementary School Teacher, 2019)
This study was aimed at knowing the development, feasibility and effectiveness of a Javanese script-based monopoly game learning medium on Javanese Language subject as a very feasible learning medium and helpful to improve the cognitive learning achievement of the fourth grade students of Islam Al madina Semarang. This study employed to Research and Development (R&D) method. The population and samples of this study were the students of class IV C of Islamic Elementary School (SD) Al Madina Semarang chosen by using random sampling. The data collection technique used by the researchers were questionnaire, interview, documentation, observation and test. Meanwhile, the data analysis was done by using the tests of validity, reliability, normality, t-Test, and N-gain. In the expert judgement phase, all experts agreed that the Javanese script-based monopoly game was very feasible to use as a learning medium with some revisions based on their feedbacks. Moreover, the feasibility percentages given by the experts were 98% from media expert, 97.8% from materials experts, and 94.3% from language expert. Further, this Javanese script-based monopoly game learning medium affected on the cognitive learning achievement of students proven by the different average scores of students understanding based on t test as many as 11.666 and average increase (N-gain) of 0.78 with high criterion. In conclusion, the Javanese script-based monopoly game learning medium is effective to be used as a learning medium.